Proceedings of the 2006 International Workshop on Software Engineering for Automotive Systems 2006
DOI: 10.1145/1138474.1138483
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with model and autocode reviews in model-based software development

Abstract: Through the introduction of model-based development, paradigm models became first class citizens in the development of invehicle software and are thus also object to strict quality assurance. Just as code reviews are widespread in classical software development, models also have to undergo a stringent review procedure -particularly if they serve as a basis for automatic software implementation by means of model-based code generators. In addition to model reviews, the generated production code (autocode) must b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…One article [17] describes a review technique applied to models. The authors present an approach for a combined model and autocode review, and typical defect types are stated (e.g., improper definition of data types, code inefficiencies).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One article [17] describes a review technique applied to models. The authors present an approach for a combined model and autocode review, and typical defect types are stated (e.g., improper definition of data types, code inefficiencies).…”
Section: Discussionmentioning
confidence: 99%
“…18 papers consider analysis, 19 papers describe test techniques applied to Matlab Simulink models, and 7 papers present combinations. 41% analysis test [3,8,10,11,16,17,18,19,20,21,22,23,24,25,29,33 Figure 4 shows the publication years of the result set. It can be seen that none of the relevant publications was published before 2000, and that 75% of the papers were published in the last five years.…”
Section: Rq1: Classification Of Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of qualified development tools is that certain safeguarding measures, like code reviews on generated code (Stürmer et al, 2006), can be omitted.…”
Section: Tool Qualificationmentioning
confidence: 99%
“…In addition, few reviewers would be capable of keeping all the modelling rules to be checked in mind. However, experience has shown that a combined model and code review can significantly improve the quality of the model used for code generation [9]. Tools such as Model Advisor are also available to help the modeller check a model with regard to the conformance of guidelines and standards (e.g.…”
Section: B Modelling In Simulinkmentioning
confidence: 99%